2021
DOI: 10.1021/acs.orglett.1c02757
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Indole Synthesis via C–H Activation and Bisamination Sequence with Diaziridinone

Abstract: This work describes an efficient Pd-catalyzed indole synthesis. A wide variety of indoles can be obtained in good yields from readily available vinyl bromides. The reaction likely proceeds through a sequential aryl C–H activation and bisamination of a resulting pallada­(II)­cycle with diaziridinone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“… , Consequently, numerous synthetic methods have been developed to access the 2-arylindole substructure. Classic routes include the Fischer indole synthesis while contemporary approaches employ transition-metal catalysts, including direct C-2 arylation of pre-existing indoles, and intramolecular cyclization of functionalized anilines, and many others. Some of these approaches employ harsh reagents, highly functionalized precursors, or cryogenic temperatures that are challenging to access on scale. Therefore, more straightforward, efficient, and practical synthetic methods without addition of transition metals for the assembly of 2-arylindoles remain in demand.…”
Section: Introductionmentioning
confidence: 99%
“… , Consequently, numerous synthetic methods have been developed to access the 2-arylindole substructure. Classic routes include the Fischer indole synthesis while contemporary approaches employ transition-metal catalysts, including direct C-2 arylation of pre-existing indoles, and intramolecular cyclization of functionalized anilines, and many others. Some of these approaches employ harsh reagents, highly functionalized precursors, or cryogenic temperatures that are challenging to access on scale. Therefore, more straightforward, efficient, and practical synthetic methods without addition of transition metals for the assembly of 2-arylindoles remain in demand.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently reported the synthesis of heteroatomrich spirocycles via a domino Mizoroki−Heck/C−H activation strategy of compounds with preinstalled heterocycles. 3b Advancing our research program in heterocycle synthesis, herein we report a domino Narasaka−Heck/C−H activation/ amination reaction using diaziridinone, 6 generating novel nitrogen-rich bis-heterocyclic spirocycles (Scheme 1C).…”
mentioning
confidence: 99%
“…Recently, we have found that di-t-butyldiaziridinone (5) can also intercept a pallada(II)heterocycle intermediate to give the ortho-aryl C-H amination product with an N-(quinolin-8-yl) benzamide substrate. 12,13 Now we report that the vinyl C-H amination process is feasible for N-(quinolin-8-yl)acrylamides, providing a variety of 3-amino-N-(quinolin-8-yl)acrylamides (Scheme 2). While the metal-catalyzed aryl C-H amination has been extensively studied, the corresponding direct vinyl C-H amination for the formation of acyclic enamines or their derivatives is surprisingly rare.…”
mentioning
confidence: 99%